HUBUNGAN SARAPAN DENGAN RISIKO OBESITAS PADA ANAK USIA SEKOLAH DI SDN ROROTAN 01 PAGI JAKARTA - Afdila (2022)
Preliminary study at SDN Rorotan 01 Pagi Jakarta as many as 5 students breakfast <4x/week and nutritional status obesity, 2 students breakfast <4x/week and normal nutritional status, 2 students breakfast >4x/week have normal nutrition poor nutritional status, and 1 students who eat breakfast <4x/week have underweight nutritional status. Nutrition plays a role as a supporter of health aspects. Skipping breakfast is closely linked to an increased risk of obesity associated with dietary elements. The type of quantitative research is Analytic Cross Sectional Study. The sample size is 132 respondents. It is known that in the normal BMI category (34.1%) have good breakfast habits, then as many as (40.2%) have bad breakfast habits. In the overweight BMI category, it is known that 23 people have good breakfast habits (17.4%) while (8.3%) have bad breakfast habits. The results of the chi square test analysis showed that there was a relationship between breakfast habits and the risk of obesity (p value <0.05). It is hoped that families or parents can pay attention to their child's nutritional intake, especially at breakfast, and look for a lot of information about balanced nutrition in children.